VD_FINDINFO Décision / 2011 / 10 vom 3. Januar 2011 - VD Tribunal cantonal (2011)
DÉFENSE D'OFFICE | 130 let. a CPP (CH), 130 let. b CPP (CH), 132 al. 1 let. a ch. 1 CPP (CH), 132 al. 2 CPP (CH), 132 al. 3 CPP (CH), 393 al. 1 let. a CPP (CH)